Penerapan Problem Based Learning dengan Menggunakan Media Peta Keberagaman Indonesia pada Mata Pelajaran IPAS untuk Meningkatkan Keaktifan Belajar Peserta Kelas IV B SD Negeri Bratan I Surakarta - Iqbal Ibnu Ganedi; Oktavia Nur Hasanah; Muhammad Ichsan Arifka Rahman; Sukarno Sukarno; Kristina Ermiyanti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
Based on the observation, it is known that IPAS learning in class IV B SD Negeri Bratan I Surakarta has low activeness so that learning becomes less interactive. This class action research aims to increase the activeness of students through the application of the Problem Based Learning (PBL) learning model and the Diversity Map learning media. The research was carried out in two cycles, each of which consisted of planning, action implementation, observation, and reflection stages, with the research subjects being 29 students of class IV B. The data collection techniques used were observation and documentation. The results of this study indicate that the application of the Problem Based Learning learning model with the Diversity Map learning media at SD Negeri Bratan I Surakarta class IV B can increase the activeness of students in IPAS subjects. The activeness of students in the pre-cycle was 20.68%, increased to 51.72% in cycle I, and increased again to 82.76% in cycle II. Thus, it can be concluded that the use of Problem Based Learning learning model with Diversity Map media is effective in increasing the activeness of students in IPAS learning in class IV B SD Negeri Bratan I Surakarta.